The politics of moral capital - Kane, John (Cambridge University Press, 2001)
John Kane argues that, despite appearances, politicians and governments care deeply about people's moral judgments, for these provide the moral capital they depend on for survival and effective functioning. Some famous leaders--Lincoln, de Gaulle, Mandela--illustrate the workings of moral capital in politics, and a study of the American presidency from Kennedy to Clinton shows how the moral capital of the United States has been eroded, with severe consequences for the nation's morale.